ANALISIS KEMAMPUAN GURU AGAMA ISLAM DALAM MENYUSUN BAHAN AJAR KURIKULUM MERDEKA PADA MI AL-FAJAR MEDAN DELI - Siti Chairun Nisyah; Siti Halimah; Fauziah Nur; Aina Nur Hilmy (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This research analyzes the ability of Islamic teachers in compiling teaching materials according to the Independent Curriculum at MI Al-Fajar Medan Deli. The Merdeka Curriculum challenges teachers' creativity in designing teaching materials that are relevant to students' needs, integrating religious values, and utilizing learning technology. The research uses qualitative descriptive methods through interviews, observation and documentation. The results show that Islamic teachers at MI Al-Fajar have good abilities in compiling teaching materials, including selecting relevant material, using various learning media, and integrating technology. Teachers are also able to adapt teaching materials to students' socio-cultural context, utilize digital platforms for interactive learning, and develop flexible lesson plans. Obstacles faced include limited intensive training and supporting resources. The strategies used include involving students in discussions and projects based on religious values, as well as increasing competence through independent training. This research makes a significant contribution to the professional development of Islamic teachers and the effective implementation of the Independent Curriculum at the Madrasah Ibtidaiyah level.